Total Hip Replacement An Overview - Bagaria, Vaibhav (IntechOpen, 2018)
The incidence of total hip arthroplasty is increasing in number because of successful outcomes. Although technically challenging, once mastered a hip replacement is one of the most gratifying surgeries for both patient and surgeon. This book covers some of the most important aspects of hip replacement surgery. These include preoperative planning, anesthesia, classification systems, management of proximal femur fractures, anterior approach, complications, and rehabilitation aspects of hip arthroplasty. The book is intended for arthroplasty surgeons, anesthetists, and physical therapists who will find the book useful in parts and as a whole if they deal with arthroplasty cases on a regular basis. Experience-based narration of various subjects by authors ensures that first-hand experience is passed on to readers in a simple, easy-to-understand manner.